2018
DOI: 10.1590/1806-9282.64.07.627
|View full text |Cite
|
Sign up to set email alerts
|

Translation and cultural adaptation of the Breast Cancer Treatment Outcome Scale (BCTOS) into Brazilian Portuguese

Abstract: SUMMARY BACKGROUND: Breast conservative treatment (BCT) is safe when it is performed in association with radiotherapy. The number of referral for BCT has increased, and it has become an important treatment modality. Patients who undergo BCT present some characteristics that are associated with better quality of life compared with patients who undergo mastectomy without reconstruction. Instruments that measure the quality of life specifically used in cases of BCT are limited. One of these instruments is the Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…The data in the medical records were retrospectively evaluated through standardized records. The BCTOS is a specific questionnaire that was translated into the Brazilian Portuguese language for use in patients who undergo BCT [25]. This questionnaire contains 22 questions divided into 4 domains (functional, cosmetic, pain, and oedema); the cosmetic domain consists of 8 questions.…”
Section: Methodsmentioning
confidence: 99%
“…The data in the medical records were retrospectively evaluated through standardized records. The BCTOS is a specific questionnaire that was translated into the Brazilian Portuguese language for use in patients who undergo BCT [25]. This questionnaire contains 22 questions divided into 4 domains (functional, cosmetic, pain, and oedema); the cosmetic domain consists of 8 questions.…”
Section: Methodsmentioning
confidence: 99%
“…All studies were conducted between 2001 and 2019 and three studies [22][23][24] were reported in non-English language publications (Refer to Table 2). While the majority of studies were conducted in Brazil (n = 12) and Turkey (n = 9), most other regions with LMIC were represented, including: South America (n = 12) [5,20,24,[32][33][34][35][36][37][38][39]49] [47,48,54] and East Asia and Pacific (n = 1) [46].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…While the majority of studies were conducted in Brazil (n=12) and Turkey (n=9), most other regions with LMIC were represented, including: South America (n=12) (5,19,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), Europe (n=11) (20,22,(33)(34)(35)(36)(37)(38)(39)(40)(41), Southern Asia (n=6) (42)(43)(44)(45)(46)(47), West Africa (n=3) (21,48,49), Middle East (n=3) (50)(51)(52) and East Asia and Pacific (n=1) (53).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%